Estudo eletrofisiológico in vitro do hipocampo e da suscetibilidade frente a dois modelos experimentais de epilepsia no roedor Trinomys yonenagae - Nascimento, André Luiz do [UNIFESP] (2009)
Trinomys yonenagae (TY) is a fossorial rodent dweller of sand dunes of the Caatinga, pertaining to Echimydae family and known locally as rabo de facho. The observation of some animals of this species show spontaneous seizures stimulated us the study of some characteristics of its nervous system that could to be subjacents to this condition. Through techniques of eletrophysiology in vitro, with the utilization of protocols of induction of hiperexcitability and study of the long-term potentiation (LTP), we aimed at to identifying the eletrophysiologic pattern of hippocampal circuitry of the TY and comparing it to Wistar rats. Additionaly, we also aimed at verifying how animals of the TY species behave regarding two classic models of epilepsy induction: amygdala kindling and systemic aplication of pilocarpine. In the high potassium protocol, we observed in TY a higher sensibility to gradual increase of potassium in the artificial cerebrospinal fluid (ACSF). In the protocol of addition of antagonist of GABAA receptor (bicuculine) in the ACSF, we did not observe any significative differences in the extracellular records between TY and Wistar. In the absence magnesium protocol in the ACSF, both species showed spontaneous epileptiform activity, and when both species were submited to electric stimulation, their responses did not differ statisticaly. In the study of LTP, we observed that, although the normalized slopes averages in TY have showed always smaller than of Wistar after high frequence stimulus, these values between the two species did not differ statistically. The electroencephalographic and behavioral data were similar between TY and Wistar in the two epilepsy induction models, with exception of the pilocarpine dosage used to elicite status epilepticus in TY, that was lower. The electrophysiological characterization and the obtained results against the epilepsy models are interesting contributions to the knowledge of the nervous system of the TY and reveal the importance to futures works in this species for the acquisition of new knowledges that can to be involved in the genesis of the seizures.